Impact of suction ureteral access sheath in ureteroscopy/retrograde intrarenal surgery: a systematic review and meta-analysis - Kayano, Sotaro; Matsukawa, Akihiro; Laukhtina, Ekaterina; Yata, Yuji; Miyajima, Keiichiro; Murakami, Masaya; Shimomura, Tatsuya; Yuen, Steffi Kar Kei; Shariat, Shahrokh F; Kimura, Takahiro; Yanagisawa, Takafumi (Translational andrology and urology, 2025)
BACKGROUND: Advances in technology have led to the introduction of the suction ureteral access sheaths (SUASs) in ureteroscopy (URS) and retrograde intrarenal surgery (RIRS), with their clinical benefits becoming widely acknowledged. We aimed to evaluate the efficacy and safety of using SUASs during URS and RIRS. METHODS: A systematic search was conducted in April 2024 across the MEDLINE, Scopus, and Web of Science databases. Our focus was on studies investigating the use of SUASs during URS/RIRS for urinary stones. To compare the stone-free rate (SFR) and perioperative outcomes between URS/RIRS procedures with and without SUASs, standard pairwise meta-analyses were conducted. Risk ratios (RRs) and mean differences (MDs) with 95% confidence intervals (CIs) were employed utilizing a random-effects model (PROSPERO: CRD42024538956). RESULTS: Seven studies (n=1,746) were identified. The use of SUASs significantly improved immediate SFR compared to non-SUAS group (RR: 1.23; 95% CI: 1.02 to 1.47; P=0.03), while no significant difference was observed in SFR at one month follow-up. The use of SUASs significantly reduced operation time (MD: -7.98 minutes; 95% CI: -13.46 to -2.50; P=0.004) and overall complication rate (RR: 0.49; 95% CI: 0.34 to 0.71; P<0.001). CONCLUSIONS: Our meta-analyses indicate that the use of SUASs during URS/RIRS significantly improves immediate SFR and offers better perioperative outcomes compared to no use of SUASs. To establish SUASs as standard of care, well-designed randomized controlled trials are needed.
Keywords: ureteroscopy (URS); retrograde intrarenal surgery (RIRS); ureteral access sheath; suction; Urinary stone